Exploring the Possibility of β‐Phase Arsenic‐Phosphorus Polymorph Monolayer as Anode Materials for Sodium‐Ion Batteries. Issue 8 (16th June 2020) - Khossossi, Nabil; Shukla, Vivekanand; Benhouria, Younes; Essaoudi, Ismail; Ainane, Abdelmajid; Ahuja, Rajeev; Babu, Ganguli; Ajayan, Pulickel M.
Abstract: Graphite anode have shown commercial success for over two decades, since the start of their use in commercial Li‐ion batteries, due to their high practical specific capacity, conductivity, and low lithiation potential. Graphite is to a large extent thermodynamically unfavorable for sodium‐ion intercalation and thus limits advancement in Na‐ion batteries. In this work, a β‐phase arsenic‐phosphorus monolayer is studied, which has recently been predicted to have semiconducting behavior and to be dynamically stable. First‐principles calculations based on density functional theory are used to explore the role of β‐AsP monolayer as a negative electrode for Na‐ion batteries. Cohesive energy, phonon spectrum, and molecule dynamics simulations confirm the thermodynamic stability and the possibility of experimentally synthesizing this material. The Na‐ion adsorption‐energies are found to be high (>−1.2 eV) on both sides (As‐ and P‐side). The ultra‐fast energy barriers for Na (0.046/0.053 V) over both sides imply high diffusion of Na‐ions on the surfaces of β‐AsP. During the evaluation of Na‐ion anode performance, the fully sodiated state is found to be Na2 AsP, which yields a high theoretical‐specific capacity of 506.16 mAh g −1 and low average sodiation potential of 0.43 V versus Na/Na+. Abstract : The selection of a stable and suitable 2D anode material is one of the main challenges towards commercialization and development of Na‐ion batteries to achieve high capacity, ultrafast diffusion with an ultrahigh rate of charging and discharging capability.